Residential segregation and interethnic contact in the Netherlands - Boschman, Sanne (A+BE | Architecture and the Built Environment, 2015)
Dutch policymakers perceive high shares of ethnic minorities in neighbourhoods as a problem; it might generate fewer opportunities for minorities to have contact with the native Dutch population and thereby hinder integration. The question, however, is whether the ethnic composition of neighbourhoods influences interethnic contact. In this paper the focus is on leisure contact of people from ethnic minorities aged 15 to 65 with native Dutch people. Binary logistic multilevel analysis shows that contact with native Dutch people is mainly explained by individual characteristics. In addition, living in one of the four largest cities, cities with high shares of minorities on city level, leads to less contact with native Dutch people. The ethnic composition of the neighbourhood has no effect on contact, therefore segregation on neighbourhood level does not necessarily hinder integration.